Optimizing the Implementation of Thematic Learning in the Independent Curriculum: As a Solution to Increase Student Engagement - Pajrini, Ani; Misnawati, Misnawati; Ayu Pertiwi, Linda; Rahmi Amanda, Ulya (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This research focuses on the implementation of thematic learning in the Independent Curriculum. This study uses a qualitative approach with a case study design that involves interviews, observations, and documentation as data collection techniques. The main sources of information consist of teachers involved in thematic learning and students who are participants in the learning. The results of the study show that thematic learning in SD Lab School Integrated can increase student engagement and make it easier for them to relate concepts from various subjects to real life. However, time management is a major challenge, due to the limited time available to complete all thematic materials and the need to coordinate multiple subjects in one theme. Nonetheless, teachers strive to address these challenges by prioritizing the most relevant activities and using a project-based approach to improve student understanding. The implication of this study is the importance of more flexible time planning and increased collaboration between teachers to optimize the implementation of thematic learning. This research contributes to enriching the literature on thematic learning and the Independent Curriculum, as well as providing practical insights for schools in implementing more contextual and relevant learning. Further research is needed to further explore other challenges in the implementation of thematic learning in various school contexts